Analysis of failure characteristics of grouting concretion body under the action of water-force coupling - Tang, Fei; Dong, Donglin; Xiao, Zhen; Guan, Zilong (Frontiers in Earth Science, 2023)
Cement slurry is widely used in grouting reinforcement of coal mine floor. Under the action of water-force coupling, the floor of abandoned roadway reinforced by cement slurry is prone to damage. The failure characteristics of grouting concretion body under water-force coupling were studied by using RFPA software considering the heterogeneity of rock mass. The numerical simulation results show that the acoustic emission (AE) of numerical samples of the same strength with different lower boundary pressure decreases with the increase of lower boundary pressure, and the acoustic emission of numerical samples of the same lower boundary pressure with different strength increases with the increase of compressive strength. The lower the water pressure at the lower boundary is, the lower the softening degree of the sample is, and the sample is more prone to brittle fracture under external load. The numerical simulation results have important guiding significance for the grouting concretion body protection of coal mine floor in the future.